Concepts of Event Loyalty and Destination Loyalty Based on the Example of Sports Fans of Poznan Half Marathon - Joanna Poczta; Ewa Malchrowicz-Mosko; Nuno Almeida (Ekonomiczne Problemy Turystyki, 2017)
This article explores the research problem of building loyalty of tourists towards sports events and tourist destinations, whose roots are in behavioral marketing. The work includes an overview of literature focused on tourist loyalty towards a sports event, and further on – towards a tourist destination. It presents the concepts which made it possible to create assumptions for conducting empirical research during the 6th Poznan Half Marathon. The aim of the study was to determine the factors influencing the spectators’ loyalty towards this event and subsequently towards the destination. The study focused on the attempt to determine whether loyalty can be built also among sports fans, because foreign language publications are typically concerned with athletes. It appears that the conducted research confirms the assumptions adopted on the basis of the literature and proves that the loyalty of a sports fan towards the event is influenced by: motivations for passive participation in the event (push and pull), socio-demographic factors, and a sense of satisfaction from supporting the athletes, who are often close to them.